Digital Election Model In The Election Of Regional Head And Deputy Head In Indonesia - Januwarso, Arief; Sukristiyanto, Agus; Darmawan, Arief (Advances in Social Sciences Research Journal, 2022)
This study aims to develop a model for digital general election in the election of Regional Head and Deputy Head. The focus of this research is on the simultaneous regional elections in 2020 in the regencies of Jember, Malang, Lamongan and Sidoarjo. In the research method, a qualitative-descriptive approach was used, with a phenomenological basis. The results of the study indicated that the legitimacy of authority in the 2020 Regional Head and Deputy Head Elections has decreased or the elections had incomplete legitimacy. This can be seen from the percentages of votes for the winners of the local elections, who received less than 50% in the regencies of Jember, Malang, Lamongan and Sidoarjo. Recommendations are offered for the development of a new regional election system, which may attain full power legitimacy, as follows. First, the digital-based electoral system needs to be improved. Second, election needs to be socialized as early as possible. Third, political education needs to be developed by political parties, through political school programs with competent teachers. Fourth, the model, which needs to be set up with a bottom-up system through full community participation, may produce a pattern of regional election that is more in line with the conditions and desires of the people so that the people can give full power (full legitimacy) for the winners to manage the regional government.